AUDIT ON ALDOSTERONE-TO-RENIN SAMPLING IN SCREENING FOR PRIMARY ALDOSTERONISM: SINGLE-CENTER, TERTIARY DISTRICT HOSPITAL EXPERIENCE - Padzil, Mohd Hafiz Mohd; See, Chee Keong; Teo, Jin An; Lau, Chia Hui; Shudim, Saiful Shahrizal (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Aldosterone-to-renin ratio (ARR) sampling is the first line investigation for detection of hyperaldosterone-driven hypertension. Clinical practice guidelines (CPG) advocate testing the ARR in specific indications with special consideration in confounding factors, especially types of antihypertensive medicine. We aimed to determine the adherence of ARR sampling as outlined by CPG. METHODOLOGY We retrospectively evaluated ARR requests taken from January 2020 till December 2024 in Hospital Sultan Haji Ahmad Shah. Demographic data associated with or without hypertension, indication for screening, interfering medications and outcomes were extracted from medical records. RESULT Out of 287 tests retrieved, only 222 were qualified for analysis. The median age was 34 (interquartile range, IQR 11) with 133 (59.9%) males. The medical duration of hypertension was 5 years (IQR 7). The majority of ARR sampling was sent for onset of hypertension less than age 40 (n = 150, 67.6%). Other indications were resistant hypertension (n = 28, 12.6%), hypertension with hypokalemia (n = 28, 12.6%), hypertension with adrenal incidentaloma (n = 4, 1.8%) and family history with hypertension onset of less than 40 or cardiovascular disease (CVD), n = 4, (1.8%). The ARR were found to be positive or indeterminate in 23 samples (10.4%): highest among cohort of hypertension with hypokalemia, n = 12 (42.9%) then adrenal incidentaloma and family history of young onset hypertension/CVD (25% each) and later was resistant hypertension, n = 4 (14.3%). Hypertension onset of less than 40 only yields a 3.3% positivity rate (n = 5). Interfering medicines did not significantly impact ARR results. Of 23 samples, 15 (65.2%) were confirmed primary hyperaldosteronism. CONCLUSION ARR sampling was overly investigated among hypertensive less than 40 years old. Adherence to indications as per guideline recommendations needs to be strengthened to prevent wasteful resources.